2006
DOI: 10.3748/wjg.v12.i27.4310
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of T cell hyporesponsiveness to HBcAg is associated with regulatory T cells in chronic hepatitis B

Abstract: The results indicate that the mechanism of T cell hyporesponsiveness to HBcAg includes activation of HBcAg-induced regulatory T cells in contrast to an increase in TH2-committed cells in response to HBsAg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 41 publications
0
49
1
3
Order By: Relevance
“…IFN-γ has a variety of important roles in the activation of a range of Th1-associated cellular immune functions in immunopathology of chronic hepatitis B (Löhr et al 1998;Kondo et al 2006). In an IFN-γ receptordeficient mouse model, IFN-γ has been approved to be indispensable (Ohta et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ has a variety of important roles in the activation of a range of Th1-associated cellular immune functions in immunopathology of chronic hepatitis B (Löhr et al 1998;Kondo et al 2006). In an IFN-γ receptordeficient mouse model, IFN-γ has been approved to be indispensable (Ohta et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation between HBeAg level, HBV DNA level and the frequency of CD4+CD25+ Treg cells in the blood of chronically infected patients further supports the role of Treg cells in HBV infection [58][59][60] . Finally, two studies showed the presence of HBcAgspecific CD4+CD25+FoxP3+ Treg cells in chronically HBV infected patients [61,62] . Interestingly, HBcAg specific CD4+CD25+ Treg cells declined in the blood of patients during acute exacerbation of hepatitis in the immunoactive phase in chronic HBV infection while the HBcAg specific CD8+ T cell frequency increased at the same time.…”
Section: Regulatory T Cells In Hbv Infectionmentioning
confidence: 99%
“…The analysis of Treg cells during acute HBV infection showed that Treg cells may also play a role in this state of the infection. Indeed, the frequency of CD4+CD25+ Treg cells was normal in the early acute phase of infection, increased during the convalescent phase and decreased [42][43][44][45][46]48,54,56,58,61,62] HCV HBV Blood/Liver Cell-cell contact dependent suppression of antigen specific and unspecific T cell proliferation and cytokine production…”
Section: Regulatory T Cells In Hbv Infectionmentioning
confidence: 99%
“…It has been shown that the innate immune system, including natural killer cells (NK cells), natural killer T cells (NK-T cells), and monocytes, and the intrahepatocyte immune reaction, in addition to the adaptive immune system, including cytotoxic T lymphocytes (CTLs), CD4 ϩ type 1 helper T cells (Th1 cells), CD4 ϩ CD25 ϩ FOXP3 ϩ regulatory T cells (Tregs), and dendritic cells (DCs), play an important role in the control of HBV (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Intrahepatocyte immune reactions can be induced by pattern recognition receptor families, including Toll-like receptors, retinoic acid-induced gene I-like receptors, and Nod-like receptors.…”
mentioning
confidence: 99%
“…Among these various kinds of immune cells, NK cells, NK-T cells, and CTLs have a potent cytotoxic function that could control HBV-infected hepatocytes and hepatocellular carcinoma (3,6,17,18). However, many groups, including us, have reported that persistent infection with HBV can suppress the effector func-tion of NK cells, NK-T cells, and CTLs by various mechanisms (8,9,(19)(20)(21)(22)(23)(24)(25). Natural killer group 2 member D (NKG2D) is one of the activating receptors on NK cells (26).…”
mentioning
confidence: 99%